Characteristics of localized surface plasmons excited on mixed monolayers composed of self-assembled Ag and Au nanoparticles. Issue 37 (2nd September 2015) - Tanaka, Daisuke; Imazu, Keisuke; Sung, Jinwoo; Park, Cheolmin; Okamoto, Koichi; Tamada, Kaoru
Abstract : AuNPs form ∼100 nm island domains in a homogeneous AgNP matrix phase in mixed monolayers, which maintain independent LSPR bands and selective fluorescence quenching. Abstract : The fundamental characteristics of localized surface plasmon resonance (LSPR) excited on mixed monolayers composed of self-assembled Ag and Au nanoparticles (AgNPs and AuNPs, respectively) were investigated. Mixed monolayered films were fabricated at the air–water interface at different mixing ratios. The films retained their phase-segregated morphologies in which AuNPs formed several 10 to 100 nm island domains in a homogeneous AgNP matrix phase. The LSPR bands originating from the self-assembled domains shifted to longer wavelengths as the domain size increased, as predicted by a finite-difference time-domain (FDTD) simulation. The FDTD simulation also revealed that even an alternating-lattice-structured two-dimensional (2D) AgNP/AuNP film retained two isolated LSPR bands, revealing that the plasmon resonances excited on each particle did not couple even in a continuous 2D sheet, unlike in the homologous NP system. The fluorescence quenching test of Cy3 and Cy5 dyes confirmed that the independent functions of AuNPs and AgNPs remained in the mixed films, whereas the AuNPs exhibited significantly higher quenching efficiency for the Cy3 dye compared with AgNPs due to the overlap of the excitation/emission bands of the dyes with the AuNP LSPR band. Various applications can be considered using this nanoheterostructured plasmonic assembly to excite spatially designed, high-density LSPR on macroscopic surfaces.